2021
DOI: 10.1111/are.15078
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic potential of autochthonous bacteria from tambaqui Colossoma macropomum

Abstract: In this study, the identification and characterization of potential probiotic bacteria present in natural microbiota of tambaqui Colossoma macromum were performed for the first time. Bacteria from the intestinal mucosa were isolated in agar Man, Rogosa and Sharpe (MRS). Only Gram‐positive and haemolysis‐negative isolates were selected (n = 152). The tests included morphological differentiation, gene sequencing, catalase, bile tolerance, pathogen antagonism, antimicrobial susceptibility and safety to the host. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
2
0
1
Order By: Relevance
“…cibaria KY10 was sensitive to tetracycline, chloramphenicol, gentamicin, polymycin B and erythromycin, but resistant to kanamycin, streptomycin and vancomycin (Table 1). Among the antibiotics tested, resistance to vancomycin is a major concern, as it is one of the few antibiotics available to treat infections caused by multidrug‐resistant pathogens (Kotzent et al, 2020). These findings are in agreement with other studies (Choi et al, 2002; Yu, Jang, et al, 2019; Yu, Lee, et al, 2019) concluding that W .…”
Section: Discussionmentioning
confidence: 99%
“…cibaria KY10 was sensitive to tetracycline, chloramphenicol, gentamicin, polymycin B and erythromycin, but resistant to kanamycin, streptomycin and vancomycin (Table 1). Among the antibiotics tested, resistance to vancomycin is a major concern, as it is one of the few antibiotics available to treat infections caused by multidrug‐resistant pathogens (Kotzent et al, 2020). These findings are in agreement with other studies (Choi et al, 2002; Yu, Jang, et al, 2019; Yu, Lee, et al, 2019) concluding that W .…”
Section: Discussionmentioning
confidence: 99%
“…Revista Multidisciplinar do Nordeste Mineiro, v.12, 2023ISSN 2178 Atualmente, existem estratégias preventivas que podem ser utilizadas para minimizar as chances de ocorrência dessas infecções zoonóticas e substituir gradativamente a utilização de antibióticos na aquacultura, na qual se destaca a suplementação dietética dos animais com probióticos, prebióticos e simbióticos (Allameh et al, 2017;Yi et al, 2018;Kotzent et al, 2021), uso de fitoterápicos (Schalch et al, 2015;Valladão et al, 2019), a vacinação e a seleção de genótipos resistentes à determinada doença (Longhi et al, 2012;Ariede et al, 2020;Zeng et al, 2021;Miani, 2022). probióticos, prebióticos e simbióticos são definidos como alimentos que estimulam o sistema imunológico dos animais a desenvolver microrganismos benéficos e a consequente diminuição do crescimento dos patogênicos.…”
Section: Revisão Da Literaturaunclassified
“…Furthermore, the genus Staphylococcus has already been indicated as a promising probiotic [15]; based on this, Ağagündüz et al [16] reported through a review article the promising potential of probiotics as prevention and treatment of certain diseases. The same author further published a review on the role of the microbiome in gastrointestinal cancer, and it was reported that some microorganisms, as well as their metabolites, are able to promote or inhibit tumorigenesis [17].…”
Section: Introductionmentioning
confidence: 99%